Narrative, Human Rights and the Ethnographic Reproduction of Conventional Knowledge - Gandsman, Ari (Anthropologica, 2013)
For anthropologists working on the topic of human rights, fieldwork often consists of collecting narratives docu menting experiences of violence and loss. Drawing on research with human organizations in Argentina, this article questions this methodological focus that is often related to human rights activism. While these narratives are often treated as organic accounts, they are also products of the human rights movement Analyses that fail to address this larger institutional context may end up reproducing conventionally held knowledge. By exploring the larger interconnections between narrative, hu man rights and trauma, I conclude by questioning the prevalent normative assumptions about narrative.